(r, Q) inventory management in complex distribution systems of the One Belt One Road initiative. (29th September 2022) - Wieczorek, Łukasz; Ignaciuk, Przemysław
The paper addresses the inventory management problem in logistic systems with a networked structure in the context of new transit corridors arising from the One Belt One Road initiative. An inventory control framework for the distribution of resources in complex multi-echelon networks governed by the ( r, Q ) inventory policy has been presented. In addition to an arbitrary topology with lateral transshipments, the demand may be imposed on any controlled node, not just end-points. The proposed framework is applied to investigate crude oil supplies for China in the presence of uncertain demand variations. The multifaceted study gives practical insights into the policy parameter selection to secure a sufficient level of resources under operational constraints. As demonstrated in numerical experiments, the constructed framework can be flexibly adapted to examine the effects of structural changes, e.g., caused by regional blockages, that enforce the reorganisation of the distribution system.